2015
DOI: 10.1021/acs.jpcc.5b07659
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Plasmons in Molecules with Scaled Ab Initio Approaches

Abstract: For the electronic excitations in metallic systems under periodic boundary conditions, momentum conservation and a uniform electron−electron interaction imply a clear distinction of plasmons and single-particle excitations. For finite molecular systems, this distinction is less clear, but excitations formed by a coherent superposition of elementary particle−hole transitions that show a collective oscillation of the transition electron density have nevertheless been identified as plasmons in molecules. To aid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
115
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(120 citation statements)
references
References 83 publications
5
115
0
Order By: Relevance
“…SCS-CIS(D) [58,59] and SOS-CIS(D) [59], SCS-CC2 and SOS-CC2 [60] or SOS-ADC(2) [12,60,61]. A comparison between ADC(2) and SOS-ADC(2) for a subset of the benchmark set employed in this study showed significant differences in the mean errors between ADC(2) and two different versions of SOS-ADC(2) [12].…”
Section: Soppa(scs-mp2) and Soppa(sos-mp2)mentioning
confidence: 73%
See 4 more Smart Citations
“…SCS-CIS(D) [58,59] and SOS-CIS(D) [59], SCS-CC2 and SOS-CC2 [60] or SOS-ADC(2) [12,60,61]. A comparison between ADC(2) and SOS-ADC(2) for a subset of the benchmark set employed in this study showed significant differences in the mean errors between ADC(2) and two different versions of SOS-ADC(2) [12].…”
Section: Soppa(scs-mp2) and Soppa(sos-mp2)mentioning
confidence: 73%
“…We note in this context that Kánná and Szalay recently reported [23] an even smaller deviation for CC2, 0.04 ± 0.012 eV, but they included only states with more than 80% single excitation character in contrast to our studies. Furthermore, in SOPPA(SOS-MP2), the excitation energies are decreased similarly to ISR-SOS-ADC(2) [12].…”
Section: Singlet Excitation Energies With the Tzvp Basis Setmentioning
confidence: 95%
See 3 more Smart Citations